PENGARUH MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUALY (SAVI) BERBANTUAN MEDIA FLASHCARD TERHADAP MOTIVASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV GUGUS V KECAMATAN KUBUTAMBAHAN - Arsini, Budi; Suryawan, IG. Agung Jaya; Wiradnyana, I Gede Arya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays a crucial role in shaping students' character, attitudes, and understanding of Pancasila values as a guide for daily life. However, conventional teaching methods often result in low student engagement and enthusiasm, leading to diminished learning motivation. Preliminary observations in the Grade IV classes of the Cluster V Elementary Schools in Kubutambahan District revealed several issues, including low active participation, a lack of student enthusiasm during lessons, and a scarcity of innovative models and interactive media in the instructional process. Consequently, there is a need for multisensory models and innovative, collaborative media to boost student learning motivation. This study aims to analyze the differential impact of the Somatic, Auditory, Visual, Intellectual (SAVI) learning model supported by flashcard media on learning motivation in Pancasila Education among Grade IV students in the Cluster V Elementary Schools of Kubutambahan District. A quasi-experimental research method with a pretest-posttest control group design was employed. The study population consisted of 122 Grade IV students from the Cluster V Elementary Schools. Simple Random Sampling was used to select the sample, resulting in 29 students from SDN 3 Tamblang serving as the experimental group and 29 students from SDN 5 Tamblang serving as the control group. Data analysis revealed a significant difference in Pancasila Education learning motivation. Hypothesis testing using the Independent Sample t-test based on N-Gain scores showed a high category score of 0.74 for the experimental group and a low category score of 0.28 for the control group. The calculated t-value (t-count) was 45.323, while the critical t-value (t-table) was 2.003; since t-count > t-table, it is concluded that there is a significant difference in Pancasila Education learning motivation between Grade IV students taught using the SAVI model with flashcard media and those taught using conventional learningmethods.